Effects of surface Chemistry, particle morphology and pretreatment on zircon flotation. (December 2022) - Wu, Yunxia; He, Jianyong; Fan, Ruihua; Wang, Qiuhao; Sun, Wei; Ralston, John; Gao, Zhiyong
Highlights: Surface chemistry, contaminations and particle morphology are responsible for the different flotation behaviors of ZV and ZH zircon. Pretreatments can improve the surface potential of zircon by increasing the exposure of ZrO2 and ZrSiO4 phases. Sodium oleate can adsorb onto zircon surfaces via ionic bonding and electrostatic attractions. Abstract: Zircon is a critical mineral for the extraction of zirconium, uranium and hafnium. Physical separation techniques like gravity and electrical separation have been widely used to obtain a commercial-grade zircon. Flotation, as a supplementary approach, can be used to separate fine zircon from heavy minerals ( i.e. rutile, cassiterite). However, it is challenging to selectively recover iron/aluminosilicate contaminated zircon, due to its low floatability. In this study, two zircon samples containing high and low amounts of impurities were selected in order to determine the influence of surface composition on flotation. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), speciation diagrams, and zeta-potentials demonstrated that pretreatment methods can improve the surface purity of zircon via the removal of coated impurities (iron-oxides and aluminosilicates) as well as increasing the exposure of the ZrO2 and ZrSiO4 phases. SEM, XPS, zeta-potential and flotation studies performed with sodium oleate (NaOL) as an environmentally benign collector show that the pretreated zircon samples display better flotation performance than the untreated zircon. First-principle calculations revealed that the chemical bond between NaOL and zircon is ionic in nature; NaOL can be both chemically and physically adsorbed onto zircon surfaces. Adsorption is mainly affected by electrostatic attractions reflected by changes in the zeta-potential. Surface pretreatment can thus substantially improve the flotation performance of zircon.